Advancing equity in global health: a call for collaborative research partnerships - Perry, Mirlene; Madundo, Kim; Narayanasamy, Shanti; Knettel, Brandon (Frontiers in Health Services, 2025)
Addressing global health challenges require collective efforts and equitable partnerships that share knowledge and resources across borders. It also requires equitable partnerships among local researchers and research participants to prevent reproducing decolonization within country. This perspective explores the multifaceted nature of partnerships in global health, examine the benefits of equitable partnerships, highlights challenges like power imbalances but also newer efforts to decolonize global health research. It also advocates for a more ethical approach in global health research to address structural inequities and promote long-term sustainability in global health initiatives across the global South.